2023
DOI: 10.1186/s13075-023-02995-y
|View full text |Cite|
|
Sign up to set email alerts
|

Pregnancy outcomes in patients receiving assisted reproductive therapy with systemic lupus erythematosus: a multi-center retrospective study

Abstract: Objectives To evaluate the safety, efficacy, and maternal and fetal outcomes of assisted reproductive therapy (ART) in systemic lupus erythematosus (SLE). Methods Patients from three tertiary hospitals from Guangzhou, China followed-up from 2013 to 2022 were included retrospectively. Patients with planned or unplanned natural pregnancy were chosen as controls. ART procedure and pregnancy outcomes were recorded and compared. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Since the beginning, pregnancies of patients with SS are considered with higher risk compared to those without SS. Elevated risk of spontaneous miscarriages is observed in these diseases [3]. The patient described in the case had a history of difficulties conceiving and had experienced two spontaneous miscarriages.…”
Section: Discussionmentioning
confidence: 91%
“…Since the beginning, pregnancies of patients with SS are considered with higher risk compared to those without SS. Elevated risk of spontaneous miscarriages is observed in these diseases [3]. The patient described in the case had a history of difficulties conceiving and had experienced two spontaneous miscarriages.…”
Section: Discussionmentioning
confidence: 91%
“…Infertility affects a significant portion of the global population, with estimates indicating that approximately 10-15% of couples encounter difficulties in conceiving. Assisted Reproductive Technologies (ART), pioneered over four decades ago, have revolutionized infertility treatment and reshaped the field of reproductive medicine (Çelik and Çalışkan, 2021;Lao et al, 2023;Wu et al, 2022). Essentially, ART encompasses a range of medical interventions designed to assist individuals or couples in achieving pregnancy when natural conception proves challenging or impossible.…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported that the e-mail address of corresponding author Zhongping Zhan is not correct. The correct e-mail address should be zhanzhp@mail.sysu.edu.cn.…”
mentioning
confidence: 99%